Preferensi dan Prilaku Mahasiswa UIN IB Padang Dalam Memilih Makanan Sudah jadi Perspektif Ekonomi Islam - Efendi, Faisal; Nashir, M.; Mardianton, Mardianton; Nurlaila, Nurlaila (Fakultas Syariah IAIN Kerinci, 2023)
The purpose of this study was to determine preferences and behavior in the view of Islamic economics towards students in choosing ready-to-eat food. This research is a field research (field research) with descriptive method. Data sources are UIN IB Padang students, business actors around the UIN IB Padang campus and the UIN IB Padang Academic community. The techniques used are observation, interviews and documentation. The results of the study are that social factors are factors that greatly influence the decisions of UIN IB Padang students in choosing fast food. This means that the majority of informants were influenced by social factors in choosing ready-to-eat food, as illustrated by the interview results, that informants were influenced by family, neighbors and colleagues who were around the campus and residence (Kos). Personality factors are factors that influence the behavior of UIN IB Padang students in choosing fast food. In general, this personality factor has an influence on students who consume prepared food, compared to other factors. this is because the color, aroma, taste, and texture of food are the main indicators for students in choosing ready-to-eat food. In choosing food for consumption, UIN IB Padang students must pay attention to aspects of Islamic Economics in consuming ready-made food such as the existing principles, namely the principles of justice, cleanliness and the principle of simplicity.